Neuropsychological Effects of Yoga Practice: A Broad Systematic Review and Meta-Analytic Synthesis of Evidence (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
Yoga has gained considerable attention in recent decades as a complementary mind–body intervention with potential benefits for cognitive functioning, emotional regulation, and brain health. The present study provides a broad systematic review and meta-analytic synthesis of approximately 1000 research publications examining the relationship between yoga practice and neuropsychological outcomes. Major academic databases including PubMed, Web of Science, Scopus, and PsycINFO were systematically searched for studies published between 2000 and 2025.After screening more than 1000 articles, 140 studies were identified as relevant empirical investigations, and 42 studies were included in quantitative meta-analysis. Results indicate that yoga practice produces moderate improvements in cognitive domains such as attention, executive functioning, and working memory. Previous meta-analytic research indicates that yoga interventions significantly improve cognitive functioning among healthy adults and older populations.Neuroimaging studies further demonstrate structural and functional changes in brain regions associated with cognitive processing, including the hippocampus, insula, prefrontal cortex, and cingulate cortex.The findings suggest that yoga promotes neuroplasticity, enhances neural efficiency, and reduces stress-related neuroendocrine responses. Overall, yoga represents a promising non-pharmacological strategy for improving neuropsychological functioning across diverse populations.